Hacia una redefinición postmoderna de la revolución política: acontecimiento, poder constituyente y disutopía - Fernández de Rota, Antón (Nómadas. Critical Journal of Social and Juridical Science, 2008)
This essay tries to approach the possibilities of the radical politics in the context of the social postmodenization. Such an approximation is realized in two times. First, I propose a narrative of the postmodern gap using the concepts Deterritorialization and Reterritorialization. To this narrative about the social change is implicit a epistemologic seated on a notion of the Constituent Power that is not separable of the Event. In the second moment, from this narrative and this epistemology, I will make a number of annotations about the possibilities of defining the political concept of the revolution in the terms and in the context of the postmodern.
Keywords: Postmodernity; Revolution; Event; Warpolitik; Multitude